El problema de las indias en la corona de Castilla. Una exégesis de Juan de Solórzano Pereira - Castaño, Sergio Raul (2018)
This article focuses on the study of the mostsignificant work of the most relevant jurist ofthe Indias, Juan de Solórzano Pereira, in orderto establish which would have been the positionof the author concerning "the most importantproblem of the Indian Law" (Zorraquín Becú):i.e., the legal-political status of the Indies as apart of the Spanish monarchy. Namely, whetherthe Indies belonged to the kingdom of Castileitself or, as the movements of 1808-1810proclaimed it in America, the Indies were onlysubject to the person of the Castilian monarch.The issue is addressed in the context ofSolórzano's doctrinal contemporary sources.The main conclusion is that Solórzanosupported the former view. Nevertheless, thisstudy ends up by analyzing a juridicalinstitution that could have fuelled the thesis of adirect and personnel link between the Indies andthe Castilian monarch.KEYWORDS: Solórzano Pereira; Ac